Randomized trial on the effects of an EMDR intervention on traumatic and obsessive symptoms during the COVID-19 quarantine: a psychometric study - Miccoli, Mario; Poli, Andrea (Frontiers in Psychiatry, 2024)
Introduction It has been suggested that the COVID-19 pandemic was a potentially traumatic occurrence that may have induced generalized anxiety and discomfort, particularly in susceptible populations like individuals with mental illnesses. The therapeutic approach known as eye movement desensitization and reprocessing (EMDR) has been shown to be successful in helping patients process traumatic events and restore wellbeing. Nevertheless, little is known about the precise processes through which EMDR fosters symptom recovery. Methods In order to disentangle these issues, we conducted a randomized controlled trial (ClinicalTrials.gov Identifier NCT06110702) with 107 participants who were selected from university hospitals as a sample of investigation. Random assignments were applied to the participants in order to assign them to the experimental and control groups. The experimental group, but not the control group, underwent an 8-week EMDR intervention. Body perception, disgust, and emotions of guilt and shame, as well as mental contamination and posttraumatic and obsessive-compulsive symptoms, were investigated before and after the EMDR intervention. Results The EMDR intervention was able to improve all of the variables investigated. Path analysis showed that body perception was able to predict both disgust and emotions of guilt and shame. Disgust was able to predict both mental contamination and obsessive-compulsive symptoms, while guilt and shame were able to predict post-traumatic symptoms. Conclusions EMDR is an effective therapy for the treatment of post-traumatic and obsessive symptoms that acts through the promotion of improvement of the emotions of guilt/shame and disgust, respectively. Implications for clinical practice are examined. Clinical trial registration https://www.clinicaltrials.gov, identifier NCT06110702.